2020
DOI: 10.15252/embj.2020106003
|View full text |Cite
|
Sign up to set email alerts
|

RAB13 mRNA compartmentalisation spatially orients tissue morphogenesis

Abstract: Polarised targeting of diverse mRNAs to cellular protrusions is a hallmark of cell migration. Although a widespread phenomenon, definitive functions for endogenous targeted mRNAs and their relevance to modulation of in vivo tissue dynamics remain elusive. Here, using single‐molecule analysis, gene editing and zebrafish live‐cell imaging, we report that mRNA polarisation acts as a molecular compass that orients motile cell polarity and spatially directs tissue movement. Clustering of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 77 publications
2
40
0
Order By: Relevance
“…Overall, our data highlight a role for local translation in directing Rab GTPase activation and suggest that the microenvironment into which a protein is synthesized can affect its regulation and downstream function. Concurrent work by Costa et al (2020) has identified a similar GA‐rich region involved in localization of the RAB13 RNA in endothelial cells and has demonstrated its importance during zebrafish blood vessel morphogenesis, further supporting the generality and physiological relevance of the mechanism described here.…”
Section: Discussionsupporting
confidence: 77%
“…Overall, our data highlight a role for local translation in directing Rab GTPase activation and suggest that the microenvironment into which a protein is synthesized can affect its regulation and downstream function. Concurrent work by Costa et al (2020) has identified a similar GA‐rich region involved in localization of the RAB13 RNA in endothelial cells and has demonstrated its importance during zebrafish blood vessel morphogenesis, further supporting the generality and physiological relevance of the mechanism described here.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, RNA accumulation is accompanied by a concentration of various RNA-binding proteins and translation factors at the leading edge and protrusions of migrating cells ( 6 9 ). RNA accumulation at protrusions is functionally relevant since preventing protrusion localization of certain RNAs or inhibiting translation at protrusions leads to protrusion destabilization and impedes the efficiency of cell migration ( 6 , 7 , 10 12 ).…”
mentioning
confidence: 99%
“…Similar to what has been described for other localized RNAs, sequences within the 3'UTR of APC-dependent RNAs are necessary and sufficient for targeting to the periphery (Mili et al, 2008). Specifically, interfering with or deleting particular GA-rich regions is sufficient to disrupt peripheral localization and perturb cell movement in various systems (Moissoglu et al, 2020;Costa et al, 2020;Chrisafis et al, 2020). Furthermore, localization to the periphery requires the microtubule cytoskeleton and in particular a subset of stable, detyrosinated microtubules (Wang et al, 2017;Moissoglu et al, 2019).…”
Section: Introductionmentioning
confidence: 70%
“…The kinesin KIF1C controls a widespread mammalian mRNA transport system RNA localization controls spatial and temporal aspects of gene expression in a variety of species and cell types. Although its significance is better understood in specialized cells such as neurons, recent reports highlight its widespread prevalence, including in cells with a mesenchymal phenotype (Mardakheh et al, 2015;Wang et al, 2017;Fazal et al, 2019;Costa et al, 2020;Chouaib et al, 2020). Our current understanding of the transport mechanisms includes the requirement of cis-acting sequence elements and trans-acting factors, which work with the actin or microtubule networks and motor proteins to bring mRNAs to their destination (Cody et al, 2013;Medioni et al, 2012;Bovaird et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation